THE ALTERATIONS OF LEUKOTRIENE-C4 AND PROSTAGLANDIN-E2 LEVELS FOLLOWING DIFFERENT ISCHEMIC PERIODS IN RAT-BRAIN TISSUE - (:unkn) unknown (CHURCHILL LIVINGSTONE, 1991)
Luekotrienes and prostaglandins are formed from arachidonic acid by activation of local phospholipases in pathological conditions such as cerebral ischemia, subarachnoid hemorrhage, cerebral tumors and seizures. These mediators, especially leukotrienes have a very potent vasoconstrictor effect on cerebral arteries.. Experimental studies have shown that this effect, by increasing vascular permeability causes vasogenic edema that contributes to the ischemic penumbra. In this study, after developing an experimental animal model simulating the concept of ischemic penumbra in the rat, the levels of leukotriene C and prostaglandin E2 produced in the forebrain were measured and the effects of these mediators in prolonged ischemia were investigated. The results, in the first 4 min of ischemia, showed that the arachidonic acid metabolites, particularly, leukotriene C4, reached a peak in the ischemic cerebral tissue in association with leukocyte accumulation. Later in the 15th min, significant decreases in leukotriene C4 and prostaglandin E2 levels were seen. In the 1st and 4th h, probably due to the stimulation of the relevant enzymes by free oxygen radicals in the ischemic tissue; the levels increase again, returning to control values by the 12th h. It is concluded that the use of lipoxygenase inhibitors and free radical scavengers may be helpful to limit the infarct area in the first 4 h of ischemia.
Keywords: CEREBRAL BLOOD-FLOW; GUINEA-PIG; EDEMA; GERBIL; BEAGLE; MODEL; ACID; REPERFUSION; ARTERIES; INJURY